Pregnant Women's Perception of Secondhand Smoke Exposure. Issue 6 (November 2022) - Artzi-Medvedik, Rada; Mohamed, Nourhan; Chertok, Ilana R. Azulay
Abstract: Background: Birth outcomes including low birth weight, preterm birth, and delayed infant neurodevelopment are associated with secondhand smoke exposure while pregnant. The purpose of the study was to explore pregnant women's perspectives on secondhand smoke exposure to understand their experience and inform recommendations. Study Design and Methods: Qualitative semistructured interviews were conducted with 15 secondhand smoke-exposed pregnant women in the United States. Results: Four primary themes were identified: feeling powerless, trapped, and discomfort; enhancing women's self-advocacy and initiative; having conflicting feelings about secondhand smoke exposure; and desiring professional advice and education. Women expressed concern about prenatal secondhand smoke exposure, although they felt unable to request that people refrain from smoking in their presence or personal space. Women's strategies to minimize secondhand smoke exposure often involved their own social isolation. Women described sources of support, educational needs, and desire for practical advice in secondhand smoke avoidance. Clinical Implications: Findings underscore the role of nurses working with pregnant women living with household members who smoke to educate women about secondhand smoke risks and strategies for avoidance and to enhance women's self-confidence in advocating for themselves to reduce their exposure. Abstract : Birth outcomes such as low birth weight, preterm birth, and delayed infant neurodevelopment are associated with secondhand smoke exposure during pregnancy. In this qualitative phenomenological study, 15 pregnant women shared their perspectives on secondhand smoke exposure. Findings underscore the role of nurses working with pregnant women living with household members who smoke to educate women about risks and strategies for avoidance and to enhance women's self-confidence in advocating for themselves to reduce their exposure.